Transitivity of the verb to be - Ferrell Ramírez, Marco A. (2015)
In analysing sentences in which the Spanish neuter pronoun lo, followed by ser [to be], was used to reproduce the meaning of transitive verbs (as in “No se pudieron desembarcar las mercaderías, pero lo fue la gente”), Andres Bello, Grand Master of Grammar, remarked in paragraph 301 of his Grammar: “The pronoun lo, which represents predicates, is the accusative case of ello”. And as he writes accusative he undoubtedly speaks of a transitive verb; so in Note VIII (“Lo” predicado) we read: “Is verb ser [to be] associated with the accusative case? Why not? Why should we shut our eyes to an obvious, indisputable fact?It’s a received principle that for a verb the fact of being active or neuter (stative) does not  depend on its meaning, inasmuch as an active verb of a tongue may correspond to a neuter verb of another tongue.” We shall build upon this idea.